Declining trend of preemptive kidney transplantation and impact of pretransplant dialysis: a Korean nationwide prospective cohort study. (28th October 2021) - Lim, Jeong‐Hoon; Jeon, Yena; Lee, Sang‐Ho; Lee, Yu Ho; Lee, Jung Pyo; Yang, Jaeseok; Kim, Myoung Soo; Jung, Hee‐Yeon; Choi, Ji‐Young; Park, Sun‐Hee; Kim, Chan‐Duck; Kim, Yong‐Lim; et al.
Summary: We evaluated the temporal trend of preemptive kidney transplantation (KT) and the effect of pretransplant dialysis duration on post‐transplant outcomes. This was a nationwide cohort study of the first‐time 3392 living donor KT (LDKT) recipients (2014–2019). The annual changes in proportion of preemptive KT, factors associated with preemptive KT, and post‐transplant outcomes were analyzed. Preemptive KT was performed in 816 (24.1%) patients. Annual trend analysis revealed gradual decrease in preemptive KT over time ( P  = 0.042). Among the underlying causes of preemptive KT, the proportion of diabetes increased and that of glomerulonephritis decreased during the study period. Glomerulonephritis as the primary renal disease was a predictor of preemptive KT. Patients with pretransplant dialysis >6 months showed increased graft failure risk than preemptive KT in the subdistribution of hazard model for competing risk (adjusted hazard ratio [aHR], 2.53; 95% confidence interval [CI], 1.09–5.87; P  = 0.031) and in propensity score‐matched analysis (aHR, 2.45; 95% CI, 1.02–5.92; P  = 0.034); however, pretransplant dialysis ≤6 months showed comparable graft survival with preemptive KT in both analyses. Preemptive KT declined over successive years, associated with an increase in diabetes and a decrease in glomerulonephritis as underlying causes of KT. Short period of dialysis less than 6 months does not affect graft survival compared with preemptive KT; however, longer dialysis decreases graft survival. Abstract : Preemptive KT declined over successive years in Korea. The proportion of diabetes increased and that of glomerulonephritis decreased among preemptive KT. Short period of dialysis less than 6 months does not affect graft survival compared with preemptive KT; however, longer dialysis decreases graft survival.